ENHANCING THE ROLE OF THE RUMAH DESA SEHAT AS A CONVERGENCE CENTER FOR ACCELERATING STUNTING MITIGATION IN MANDAILING NATAL REGENCY - Puansah, Irman; Pulungan, Darman Syah; Saputra Harahap, Rahmat Haris; Baroroh, Riski (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The high prevalence of stunting in Mandailing Natal Regency, although showing a declining trend in recent years, remains above the national target and therefore requires accelerated efforts through a convergence-based approach at the village level. This study aims to analyze the effectiveness of the implementation of the Rumah Desa Sehat (RDS) as a convergence center for accelerating stunting mitigation, identify its supporting and inhibiting factors, and formulate strategies for strengthening the institutional capacity of RDS. This research employed a qualitative descriptive method with data collected through in-depth interviews, participatory observations, and document analysis involving local government officials, village governments, health workers, Kader Pembangunan Manusia (KPM), and posyandu cadres. Data analysis was conducted using the interactive model of Miles & Huberman, consisting of data condensation, data display, and conclusion drawing. The findings reveal that RDS functions as a multisectoral coordination platform, a center for nutrition education, and a space for integrating various health services such as integrated posyandu and child growth monitoring. However, its implementation has not yet been optimal due to limited budget allocation, low human resource capacity, weak institutional documentation, and limited community participation. This study concludes that strengthening RDS requires dedicated financial support, clear institutional regulations, continuous capacity-building for cadres, stronger integration with the puskesmas, and improved community nutrition literacy. Optimizing the role of RDS is crucial for accelerating the reduction of stunting and reinforcing village-based health governance.